PWE-259 The efficacy of methotrexate in Crohn's disease: a clinical perspective. (28th May 2012) - Gordon-Walker, T T; Stahl, M W; Groome, M; Todd, J; Reynolds, N; Mowat, C
Abstract : Introduction: Methotrexate (MTX) has been shown in clinical trials to be effective in the induction and maintenance of remission in Crohn's Disease (CD). It is predominantly used in patients intolerant of, or whose disease is refractory to, thiopurine treatment. It was our aim to examine, in a clinical setting, the efficacy and side-effect profile of MTX in patients with CD. Methods: A retrospective audit was performed by casenote review of all patients with CD attending the clinical investigations unit at Ninewells Hospital to commence parenteral MTX during the period 1 January 2007 to 31 December 2010. A total of 53 patients were identified, for whom casenotes were available in 52 (26 male/26 female). Intramuscular MTX treatment was initiated at a dose of 25 mg once weekly for 16 weeks, followed by oral MTX at a dose of 15 mg once weekly. Clinical response by physician's global assessment was recorded at 3, 6 and 12 months. Clinical response was defined as complete response (absence of IBD symptoms or complete healing of fistulae); partial response (symptomatic improvement but ongoing symptoms); or no response (no improvement or deterioration from baseline). Relapse was defined as deterioration in symptoms necessitating additional medical or surgical intervention. Results: Median age of starting MTX was 32 (range 15–73). 51 of 52 patients had previously received thiopurine treatment. 12-month follow-up data were available for 48 patients. 34 patients were taking steroids at the time of initiating MTX. At 12 months, complete response was reported in 8 patients (17%), partial response in 6 patients (13%), no response in 21 patients (44%) and drug withdrawal due to side effects in 13 patients (27%). Relapse was reported in 17 patients (35%). 10 patients (21%) required additional medical therapy (steroids or biological therapy). Surgical intervention was required in seven patients (15%). Steroid withdrawal at 1-year, without recourse to biological or surgical therapy, was reported in only 11 of 34 patients (32%). MTX-associated side effects were reported in 25 patients (48%). Reported side effects included: LFT abnormalities (9), nausea (8), lymphopenia (5), lethargy (3) and mouth ulceration (1). Monitoring of FBC/LFTs was performed at 97% of scheduled weekly intervals for patients receiving parenteral MTX and at 74% of scheduled monthly intervals for patients on oral MTX. Conclusion: In this cohort, the clinical effectiveness of MTX in the induction and maintenance of remission of CD was limited. Only 29% of patients had either a complete or partial response to therapy at 1-year. The clinical effectiveness of MTX was limited by side-effects in 27%. On the basis of these results we should re-consider the position of MTX in the management of CD. Competing interests: None declared.